About Subjectivity of a University Student in Educational Activity - B. E. Fishman (Высшее образование в России, 2019)
The subjectivity of a university student in educational activities is considered as a significant factor of the compliance between the existing state of the university educational system and the requirements placed on it. The article focuses on the imbalance of information support of educational activities, the lack of personal characteristics of students in this provision. First of all, this refers to the indicators of students’ development processes, their value systems, and the choice of activity strategies. A review of the results of empirical studies that characterize students in the current educational situation is carried out. As part of a study aimed at identifying students’ individual academic strategies, a technique has been proposed to define the value-semantic determination of student activity. This method enables determining the student’s value preferences in the space of possible components of his activity. The student performs pair comparisons of the various components of his activity and in each pair chooses the component that is more important for him. According to the results of comparisons, a hierarchy for each student is determined which reflects his value preferences in the space of possible activity. The analysis of such hierarchies indicates that only 27,6% of students characterize the dominance of the processes of formation of their subjectivity. At the same time, 52,6% of students show incomplete personal subjectivity. And 19,8% of students in their activities are guided by the existing situation and external stimulation. The analysis of the general hierarchy reflecting the value preferences of the considered sample of students in the space of possible activities was performed.